Analisis Linguistik dalam Al-Qur’an (Studi Semantik Terhadap Qs Al-‘Alaq) - Raudatussolihah, Baiq; Ritazhuhriah, Ritazhuhriah (IAIN Bone, 2020)
This research aims at investigating kinds of meaning and sense relation contained in QS al-‘Alaq according to commentators. This research used qualitative method which was focused on library research. This research used a multidisciplinary approach which seeks to study and discuss objects from several disciplines or relate them to different disciplines i.e interpretive and semantics approaches. The data collected was proceed using qualitative research method and used descriptive analysis technique for data analysis and interpretation. Semantics is to study the meaning of each word that is used as interpretation Word to interpret the verses in QS al-‘Alaq according to some commentators based on semantics theory in general. The result of the study showed that kinds of meaning that was used by commentators in interpreting verses in QS al-‘Alaq consisted of some kinds of meaning, they are reference meaning, root or dictionary meaning, connotative meaning and denotative meaning. Meanwhile the sense relation between verses and the interpretation occurred in four kinds of relation namely synonymy, polysemy, hyponymy, and hypernymز Discussion about semantics studies is certainly very broad, particularly when using tafsir book as the object of study. Hence this research hopefully can become a reference for other researchers especially those who are involved in the field of Arabic in order to always study and examine arabic works including tafsir book. In addition, this research is expected to give contribution to the development of science.